2018
DOI: 10.1128/aac.00280-18
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of Single and Multiple Doses of Relebactam, a β-Lactamase Inhibitor, in Combination with Imipenem and Cilastatin in Healthy Participants

Abstract: Relebactam is a novel class A and C β-lactamase inhibitor that is being developed in combination with imipenem-cilastatin for the treatment of serious infections with Gram-negative bacteria. Here we report on two phase 1 randomized, double-blind, placebo-controlled pharmacokinetics, safety, and tolerability studies of relebactam administered with or without imipenem-cilastatin to healthy participants: (i) a single-dose (25 to 1,150 mg) and multiple-dose (50 to 625 mg every 6 h [q6h] for 7 to 14 days) escalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 31 publications
3
52
0
Order By: Relevance
“…IMI‐REL pharmacokinetic properties are summarized in Table 2. Researchers studied the effects of single and multiple doses of IMI‐REL in 106 healthy adult males, 16 elderly patients, and 8 healthy adult females . The healthy adult males were aged 18–45 years, weighed ≥ 60 kg, had a body mass index (BMI) ≤ 30 kg/m 2 , and had a CrCL > 80 ml/minute.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 4 more Smart Citations
“…IMI‐REL pharmacokinetic properties are summarized in Table 2. Researchers studied the effects of single and multiple doses of IMI‐REL in 106 healthy adult males, 16 elderly patients, and 8 healthy adult females . The healthy adult males were aged 18–45 years, weighed ≥ 60 kg, had a body mass index (BMI) ≤ 30 kg/m 2 , and had a CrCL > 80 ml/minute.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The subject who was unable to complete the study reported nausea, vomiting, and diarrhea. Two phase I, randomized, double‐blind, placebo‐controlled studies of relebactam with and without imipenem were completed in 106 and 24 healthy subjects, respectively . Study one consisted single and multiple doses (parts I–IV) administered to adult men, and study two was a multidose study in adult women as well as elderly men and women.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 3 more Smart Citations